Kinder schützen, Familien stärken Erfahrungen und Empfehlungen für die Ausgestaltung Früher Hilfen aus der "Pro Kind"-Praxis und -Forschung - Brand, Tilman; Jungmann, Tanja (Edition Sozial, 2013)
The peculiarity of the work is that different areas of the implementation quality of early help for socially disadvantaged families are considered in a differentiated way, both from the point of view of practice and from implementation research. This is done using the specific example of the home visit program "Pro Kind", in which midwives and social workers are the project actors in the field who visit the families at home every two weeks. Family accompaniment begins during pregnancy and ends on the child's second birthday